2014
DOI: 10.1016/j.heares.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Natural variability in species-specific vocalizations constrains behavior and neural activity

Abstract: A listener’s capacity to discriminate between sounds is related to the amount of acoustic variability that exists between these sounds. However, a full understanding of how this natural variability impacts neural activity and behavior is lacking. Here, we tested monkeys’ ability to discriminate between different utterances of vocalizations from the same acoustic class (i.e., coos and grunts), while neural activity was simultaneously recorded in the anterolateral belt region (AL) of the auditory cortex, a brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…For example, AL neurons respond categorically, and in a manner consistent with listeners' behavioral reports, to morphed versions of two speech sounds (“bad” and “dad”). AL neurons also respond categorically to species-specific vocalizations; however, the degree to which AL (and listen-ers) can categorize these vocalizations is constrained by the vocalizations' acoustic variability ( Christison-Lagay et al 2014 ). In humans, the superior temporal gyrus is categorically and hierarchically organized by speech sounds ( Binder et al 2000 ; Chang et al 2010 ; Leaver and Rauschecker 2010 ): phoneme categories are found in the middle aspect; word categories in the anterior-superior aspect; and phrases in the most anterior aspect ( DeWitt and Rauschecker 2012 ; Rauschecker 2012 ).…”
Section: Category Representation In the Ventral Auditory Pathwaymentioning
confidence: 99%
“…For example, AL neurons respond categorically, and in a manner consistent with listeners' behavioral reports, to morphed versions of two speech sounds (“bad” and “dad”). AL neurons also respond categorically to species-specific vocalizations; however, the degree to which AL (and listen-ers) can categorize these vocalizations is constrained by the vocalizations' acoustic variability ( Christison-Lagay et al 2014 ). In humans, the superior temporal gyrus is categorically and hierarchically organized by speech sounds ( Binder et al 2000 ; Chang et al 2010 ; Leaver and Rauschecker 2010 ): phoneme categories are found in the middle aspect; word categories in the anterior-superior aspect; and phrases in the most anterior aspect ( DeWitt and Rauschecker 2012 ; Rauschecker 2012 ).…”
Section: Category Representation In the Ventral Auditory Pathwaymentioning
confidence: 99%
“…For example, AL neurons respond categorically, and in a manner consistent with listeners' behavioral reports, to morphed versions of two speech sounds ("bad" and "dad"). AL neurons also respond categorically to species-specific vocalizations; however, the degree to which AL (and listeners) can categorize these vocalizations is constrained by the vocalizations' acoustic variability (Christison-Lagay et al 2014). In humans, the superior temporal gyrus is categorically and hierarchically organized by speech sounds (Binder et al 2000;Leaver and Rauschecker 2010): phoneme categories are found in the middle aspect; word categories in the anterior-superior aspect; and phrases in the most anterior aspect Rauschecker 2012).…”
Section: Category Representation In the Ventral Auditory Pathwaymentioning
confidence: 99%
“…The effect will depend on the particular temporal statistics of each vocalization class. Indeed, previous work has report higher variability between coos as compared to other vocalization classes [20], perhaps explaining the higher discrimination performance for the coo class. It is possible that the discriminatory differences that are absent the five slowest features that we used may be present in the next fastest features of SFA.…”
Section: Resultsmentioning
confidence: 99%
“…We chose these classes because they had the most unique exemplars, and thus we could generate the most training data for them. This library encompasses a substantial fraction of the natural variability inherent in rhesus vocalizations [20], although it is not a complete sampling. Vocalizations were recorded at 50 kHz.…”
Section: A Auditory Stimulimentioning
confidence: 99%